Progressive strength training restores quadriceps and hamstring muscle strength within 7 months after ACL reconstruction in amateur male soccer players - Welling, W.; Benjaminse, A.; Lemmink, K.; Dingenen, B.; Gokeler, A. (Physical Therapy in Sport, 2019)
Soccer players after ACLR showed similar muscle strength at 7 months compared to controls. Sixty-five percent of soccer players after ACLR passed LSI >90% for quadriceps muscle strength at 10 months. Soccer players after ACLR showed good self-reported knee function at 10 months. The purpose of the current study was to compare the results of a progressive strength training protocol for soccer players after anterior cruciate ligament reconstruction (ACLR) with healthy controls, and to investigate the effects of the strength training protocol on peak quadriceps and hamstring muscle strength. DESIGN: Between subjects design. Setting: Outpatient physical therapy facility. Participants: Thirty-eight amateur male soccer players after ACLR were included. Thirty age-matched amateur male soccer players served as control group. Main outcome measures: Quadriceps and hamstring muscle strength was measured at three time points during the rehabilitation. Limb symmetry index (LSI) > 90% was used as cut-off criteria. RESULTS: Soccer players after ACLR had no significant differences in peak quadriceps and hamstring muscle strength in the injured leg at 7 months after ACLR compared to the dominant leg of the control group. Furthermore, 65.8% of soccer players after ACLR passed LSI >90% at 10 months for quadriceps muscle strength. CONCLUSION: Amateur male soccer players after ACLR can achieve similar quadriceps and hamstring muscle strength at 7 months compared to healthy controls. These findings highlight the potential of progressive strength training in rehabilitation after ACLR that may mitigate commonly reported strength deficits.